Growth of children with thalassemia (Bangladesh Journal of Medical Science, 2014)
Background: Present observational study, to surveying the growth of children with thalassemia from Solapur District, Maharashtra State, India. Aims: The purpose of this article is to determine the growth of thalassemia in children by analyzing age and gender. One hundred twenty five thalassemic childrens with age 6 months to 18 Years, coming for to get blood transfusion from different parts of Solapur district during June 1st , 2009 to May 1st, 2013. The questionnaires included general information, medical and dental history. Results: This clinical research studied 125 patients, 73 males and 52 females. The growth of thalassemic children was observed and compared with Indian Standard Height Chart. Normal growth was: male (13.61%), female (19.23%) avarage (16.00%); growth retardation was: male (86.30%), female (80%) averages (84.00%) were observed. Conclusions: Thalassemia major is a serious medical problem. Growth retardation is commonly seen in poly-transfused beta thalassemia patients. DOI: http://dx.doi.org/10.3329/bjms.v14i1.16149 Bangladesh Journal of Medical Science Vol.14(1) 2015 p.22-25